Jaw-muscle architecture and mandibular morphology influence relative maximum jaw gapes in the sexually dimorphic Macaca fascicularis. Issue 82 (May 2015) - Terhune, Claire E.; Hylander, William L.; Vinyard, Christopher J.; Taylor, Andrea B.
Abstract: Maximum jaw gape is a performance variable related to feeding and non-feeding oral behaviors, such as canine gape displays, and is influenced by several factors including jaw-muscle fiber architecture, muscle position on the skull, and jaw morphology. Maximum gape, jaw length, and canine height are strongly correlated across catarrhine primates, but relationships between gape and other aspects of masticatory apparatus morphology are less clear. We examine the effects of jaw-adductor fiber architecture, jaw-muscle leverage, and jaw form on gape in an intraspecific sample of sexually dimorphic crab-eating macaques ( Macaca fascicularis ). As M. fascicularis males have relatively larger maximum gapes than females, we predict that males will have muscle and jaw morphologies that facilitate large gape, but these morphologies may come at some expense to bite force. Male crab-eating macaques have relatively longer jaw-muscle fibers, masseters with decreased leverage, and temporomandibular joint morphologies that facilitate the production of wide gapes. Because relative canine height is correlated with maximum gape in catarrhines, and males have relatively longer canines than females, these results support the hypothesis that male M. fascicularis have experienced selection to increase maximum gape. The sexes do not differ in relative masseter physiologic cross-sectional area (PCSA), but males compensate for a potential trade-off between muscle excursion versus muscle force with increased temporalis weight and PCSA. This musculoskeletal configuration is likely functionally significant for behaviors involving aggressive canine biting and displays in male M. fascicularis and provides additional evidence supporting the multifactorial nature of the catarrhine masticatory apparatus. Our results have implications for the evolution of craniofacial morphology in catarrhine primates and reinforce the importance of evaluating additional factors other than feeding behavior and diet in analyses of masticatory apparatus form, function, and evolution.